Quranic Christology in Late Antiquity. ‘Isa ibn Maryam and His Divine Power (Energeia) in the Islamic Revelation - Marco Demichelis (Religions, 2021)
Christology and monotheism have been dogmatically linked in the long history of Islam-Christian dialogue since the beginning of the 8th century. The Qur’an, in an analytical perception of religious otherness, specifically in relation to Christianity, assumed a dual discernment: on the one hand, it adopts a sceptical position because Christians are assimilationist (2: 120, 135, 145; 5: 51), sectarian and made Jesus the son of God (4: 171; 5: 14–19, 73; 9: 30; 18: 4–5; 21: 26); on the other hand, they are commended over the Jews and ‘Isa ibn Maryam has been strengthened with the Holy Spirit by God himself (2: 59, 62, 87, 253; 3: 48; 5: 47, 73, 82, 85, 110). The importance of enforcing the consciousness of a Quranic Christology, specifically where it concerned the potential influence that Christological doctrines such as adoptionism and monoenergism had on early Islam in late antiquity, where it was based on the proto- Islamic understanding of Jesus, and where it was rooted in Patristic orthodox-unorthodox debates, fell into oblivion. How was the Quranic canonization process affected by the ongoing Christological debates of the 7th century? Could Heraclius’ monoenergism have played a concrete influence on Quranic Christology? And in which way did early Kalam debates on God’s speech and will remain linked to Quranic Christology?